Congenital glaucoma as a presenting feature of Rubinstein-Taybi syndrome in an infant with a novel pathogenic variant in the CREBBP gene. Issue 1 (18th January 2023) - Snehi, Sagarika; Kaur, Anupriya; Chaudhry, Chakshu; Kaushik, Sushmita
Abstract : Rubinstein-Taybi syndrome, also known as broad thumb-hallux syndrome, is a rare autosomal dominant genetic disorder. This multiorgan syndrome is linked to a pathogenic mutation in the CREBBP or EBP300 genes. We present a patient with a hitherto unreported constellation of anterior segment abnormalities, including congenital glaucoma, congenital corneal keloid, cataract, and distinct facial and systemic features including a high-arched palate, low-set posteriorly rotated ears, Café-au-lait spots on the back, broad terminal phalanges of hands and feet, and bilateral cryptorchidism. The characteristic dysgenetic angle features and ultrasound biomicroscopic findings described in this case report show the occurrence of concomitant congenital keloid with glaucoma. Genetic testing revealed a heterozygous one-base pair duplication in exon 3 of the CREBBP gene (c.886dupC), a novel frameshift pathogenic mutation in the CREBBP gene that has not been previously reported in a clinical setting.